Characterization of Eco-Friendly Self-Standing Films Based on Cashew Nut Shell Liquid and Polyaniline - Aguiar, Francílio Vieira; Amorim, Daniel Roger Bezerra; Bandeira, Rafael Marinho; da Silva Guimarães, Iran; Job, Aldo Eloizo [UNESP]; Agostini, Deuber [UNESP]; Vega, Maria Leticia; da Cunha, Helder Nunes (Springer Nature, 2023)
In this work, structural, spectroscopic, and electrical characterizations of self-standing films comprising polyaniline (PANI) and a natural eco-friendly material, cashew nut shell liquid (t-CNSL), were carried out. The films were studied by atomic force microscopy (AFM), infrared spectroscopy (FTIR), thermal analyses (TGA), dynamic mechanical analyses (DMA), X-ray diffraction (XRD), and electrical impedance spectroscopy. The wt.% of t-CNSL in the films varied from 0 to 60%. The 3D images from AFM revealed a significant increase in the roughness of the films at high concentrations as a result of weak chemical interactions between the PANI and t-CNSL. The FTIR data indicate that chemical interaction between PANI/t-CNSL might be occurring possibly due to a second doping mechanism caused by t-CNSL in the film. TGA analyses showed that the addition of t-CNSL improves the thermal stability of the films. From the DMA results, we observed a small decrease of the glass transition temperature as t-CNSL is incorporated into the films. XRD diffractogram indicates slight variations in the arrangement of molecules/chains of the films due to the t-CNSL. The electrical measurements showed that films containing more than 10% of t-CNSL exhibit superior conductivity in comparison to neat PANI films in particular for 50% of t-CNSL in which the conductivity reaches the maximum value. These results show that t-CNSL acts as both plasticizer and dopant agent in PANI-based films, providing an environmentally friendly way to increase the conductivity on blending PANI.
Keywords: Cashew nut shell liquid; Conductivity; Films; Polyaniline